AN ITEM ANALYSIS OF ENGLISH SUMMATIVE TEST FOR THE TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 3 JAKARTA IN THE 2013/2014 ACADEMIC YEAR - Anisa Fitriani Lailamsyah; Fitri Apriyanti (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2020)
This research is intended to analysis of the English summative test for the tenth grade students of SMA Muhammadiyah 3 Jakarta in the 2013/2014 academic year. The research method used to analyze the item of English summative test for senior high school are quantitative and qualitative method. Quantitative method was used to analyze data of the facility value and discriminating power of each item. The qualitative method was used to describe and analyze the quality of test items. Keywords: Item Analysis, English Summative Test, Tenth Grade Student